G128 Why did my baby die? Bereaved parents' understanding of cause of death. (7th April 2014) - Garstang, JJ; Griffiths, FE; Sidebotham, P
Abstract : Aims: Since 2008, in England, all unexpected infant deaths must be investigated jointly by police, health and social services aiming to establish the full cause and relevant contributory factors for the death. This study aims to learn of bereaved parents' experiences of this joint agency approach (JAA) and their understanding of the cause and contributory factors for their infant's death. Methods: Bereaved parents, whose unexpected infants' deaths were investigated by a JAA were eligible to participate in the study. Case records from all agencies were analysed, JAA professionals were interviewed and parents were invited to complete questionnaires or have in-depth interviews. Qualitative data were analysed using a Framework Approach. Results: There were 101 eligible families of whom 23 were recruited, 16 families had in-depth interviews, 5 completed questionnaires and 2 allowed case note access only. 27 Professionals were interviewed. The median time between infants' deaths and interview or questionnaire completion was 33 weeks; all interviews took place between 2011–3. 7 cases had a medical cause for death, 16 cases were classified as SIDS or unascertained. The JAA determined modifiable contributory factors in 15/16 SIDS or unascertained deaths but in only 1 medically explained death. Learning the cause for the death was very important to most families. While most parents understood medical causes for the death; the concept of SIDS or unascertained deaths was more difficult. Despite this, several parents did have a good understanding of the relevant modifiable contributory factors for their infant's death even when these related to parental actions such as co-sleeping. However, often parents seemed to either not understand the role of these actions or failed to disclose them. Some parents blamed themselves for the death, blamed health care professionals or felt blamed by professionals. Self–blame was not related to cause of death or parental understanding of contributory factors but associated with parental anxiety and depression. Conclusion: After SIDS or unascertained deaths, parents do not always understand the cause of death and relevant contributory factors. When parents understand these issues, professionals can be reassured that this does not result in parents blaming themselves.